Yielding profits? Low adoption of an improved mung bean seed variety in Southern Bangladesh - de Brauw, Alan; Kramer, Berber; Murphy, Mike (International Food Policy Research Institute, 2020)
Agricultural technology adoption is an important driver of rural poverty reduction. We study take-up of a specific technology: BARI-Mung 6 (BM6), an improved mung bean seed variety, among smallholder farmers in the southern region of Bangladesh. In contrast to agronomic studies on BM6 performance under highly controlled conditions, we focus on performance of this variety for farmers who are growing outside of the context of an agronomic field trial. We find no evidence of higher performance in this uncontrolled environment: we do not observe statistically significant differences in output or yields between farmers planting BM6 and those planting local varieties. We do, however, observe a significant positive association between BM6 use and yields among farmers who report applying seeds within recommended guidelines. Using a simple model, we illustrate that modest uncertainty around the required quantity of seed per unit area of land can substantively impact the profitability of BM6 seeds for smallholders in our study context. Our findings highlight the importance of providing adequate extension information along with improved technologies to encourage adoption and ultimately improve farmer welfare.